2001
DOI: 10.1177/030089160108700409
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus Infection and Overexpression of P53 Protein in Bilharzial Bladder Cancer

Abstract: HPV may thus be implicated in the etiology of bilharzial bladder cancer, but a definite causal relationship remains to be demonstrated. HPV together with p53 alterations work in synergy to accelerate the carcinogenic process, as there was concordance in the results of both parameters in 24/41 (58.5%) cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…PBF (buffy coat) from these patients was uniformly negative by both real-time QPCR and MassARRAY (data not shown). Table 5) with older in situ hybridization data (4) and TaqMan data for a standard 40 cycles (left side of Table 5) show that MassARRAY is more sensitive than either in situ hybridization or TaqMan QPCR. The lack of reproducibility of the data on the left side of Table 5 (data not shown) indicates that the TaqMan technique is operating at the limits of its sensitivity and is not accurate.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…PBF (buffy coat) from these patients was uniformly negative by both real-time QPCR and MassARRAY (data not shown). Table 5) with older in situ hybridization data (4) and TaqMan data for a standard 40 cycles (left side of Table 5) show that MassARRAY is more sensitive than either in situ hybridization or TaqMan QPCR. The lack of reproducibility of the data on the left side of Table 5 (data not shown) indicates that the TaqMan technique is operating at the limits of its sensitivity and is not accurate.…”
Section: Resultsmentioning
confidence: 92%
“…(i) All 27 schistosomiasis-associated bladder cancers were associated with HPV-16 DNA, whereas a less-sensitive in situ hybridization technique detected only one-half of these associations (4). All samples reacted with the HPV-16 DNA probe and not the HPV-18 DNA probe.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results suggest that 'high-risk' HPV 16 and 18 carries a risk for the development of malignancy in the urinary tract. HPV positivity has been found more frequently in squamous than in transitional cell carcinoma [155]. Among patients with transitional cell carcinoma, HPV 16 [147] and 18 [150,162] have been the most frequently detected HPV types, indicating that 'high-risk' HPVs play a causative role in transitional cell carcinoma of bladder.…”
Section: Hpv and Urothelial Cancermentioning
confidence: 99%
“…The overall and 'high-risk' HPV infections in neoplastic specimens were distributed almost equally in male and female patients [180]. Several studies have shown geographical differences [155]. Koilocytosis has been shown to be a good morphological marker for HPV DNA in the urothelium [166], with a positive predictive value of 84.6% [146].…”
Section: Hpv and Urothelial Cancermentioning
confidence: 99%